State-Citizen Relations in Global Environment Issue: Dampak dan Upaya Penyelesaian Konflik Sosial pada Jalur Tambang Pasir di Kabupaten Mamuju - Wandi Abbas (Universitas Islam Darul Ulum Lamongan, 2025)
Global environmental issues increasingly position natural resource governance as a critical arena shaping state–citizen relations. Sand mining activities, while supporting infrastructure development, frequently generate social conflicts due to environmental degradation, infrastructure damage, and the limited involvement of local communities in decision-making processes. Mamuju Regency, West Sulawesi, represents a local context where social conflict has emerged along sand mining transportation routes that intersect residential areas and public spaces. This study aims to analyze the dynamics of state–citizen relations in sand mining governance, identify the social and environmental impacts of these conflicts, and examine conflict resolution efforts within the framework of global environmental issues and sustainable development. This research adopts a qualitative approach using a case study design. Data were collected through in-depth interviews with affected community members, local government officials, and sand mining operators, complemented by field observations along sand mining routes and document analysis of policies, environmental impact assessment reports, and media coverage. Data were analyzed thematically to identify patterns of interaction among actors, forms of social conflict, and government policy responses. The findings reveal that social conflict along sand mining routes in Mamuju Regency is driven by environmental degradation and infrastructure damage, increased risks to community safety, and low levels of transparency and public participation in mining governance. State–citizen relations tend to be top-down and reactive, with the state prioritizing regulatory and security-oriented approaches over participatory dialogue. This pattern has contributed to declining public trust in local government and prolonged conflict escalation. The study concludes that strengthening collaborative state–citizen relations through inclusive, accountable, and participatory environmental governance is essential for resolving sand mining conflicts and ensuring sustainable natural resource management at the local level.